Pemodelan Data Time Series Garch(1,1) Untuk Pasar Saham Indonesia - Elfa Rafulta -; Roni Tri Putra (Jurnal Ilmiah Poli Rekayasa, 2015)
This paper introduced a method pengklusteran for financial data. By using the model Heteroskidastity Generalized autoregressive conditional (GARCH), will be estimated distance between the stock market using GARCH-based distance. The purpose of this method is mengkluster international stock markets with different amounts of data.